Role of the C-terminal domain in inactivation of brain and cardiac sodium channels - Mantegazza, Massimo (The National Academy of Sciences, 2001)
Inactivation is a fundamental characteristic of Na(+) channels, and small changes cause skeletal muscle paralysis and myotonia, epilepsy, and cardiac arrhythmia. Brain Na(v)1.2a channels have faster inactivation than cardiac Na(v)1.5 channels, but minor differences in inactivation gate structure are not responsible. We constructed chimeras in which the C termini beyond the fourth homologous domains of Na(v)1.2a and Na(v)1.5 were exchanged. Replacing the C-terminal domain (CT) of Na(v)1.2a with that of Na(v)1.5 (Na(v)1.2/1.5CT) slowed inactivation at +40 mV ≈2-fold, making it similar to Na(v)1.5. Conversely, replacing the CT of Na(v)1.5 with that of Na(v)1.2a (Nav1.5/1.2CT) accelerated inactivation, making it similar to Na(v)1.2a. Activation properties were unaffected. The voltage dependence of steady-state inactivation of Na(v)1.5 is 16 mV more negative than that of Na(v)1.2a. The steady-state inactivation curve of Na(v)1.2a was shifted +12 mV in Na(v)1.2/1.5CT, consistent with destabilization of the inactivated state. Conversely, Na(v)1.5/1.2CT was shifted −14 mV relative to Na(v)1.5, consistent with stabilization of the inactivated state. Although these effects of exchanging C termini were consistent with their effects on inactivation kinetics, they magnified the differences in the voltage dependence of inactivation between brain and cardiac channels rather than transferring them. Thus, other parts of these channels determine the basal difference in steady-state inactivation. Deletion of the distal half of either the Na(v)1.2 or Na(v)1.5 CTs accelerated open-state inactivation and negatively shifted steady-state inactivation. Thus, the C terminus has a strong influence on kinetics and voltage dependence of inactivation in brain Na(v)1.2 and cardiac Na(v)1.5 channels and is primarily responsible for their differing rates of channel inactivation.